2018
DOI: 10.1002/hyp.13341
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of scenario‐neutral approaches for estimation of climate change impacts on flood characteristics

Abstract: Scenario-neutral assessments of climate change impact on floods analyse the sensitivity of a catchment to a range of changes in selected meteorological variables such as temperature and precipitation. The key challenges of the approach are the choice of the meteorological variables and statistics thereof and how to generate time series representing altered climatologies of the selected variables. Different methods have been proposed to achieve this, and it remains unclear if and to which extent they result in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 30 publications
0
19
0
1
Order By: Relevance
“…The Mediterranean region is a transitional zone between dry and wet climates, and in these semiarid areas the direct evaporation from the soil plays an important role on the surface energy balance, with evapotranspiration strongly dependent on available soil moisture (Koster et al, 2004;Seneviratne et al, 2010;Taylor, 2015). Consequently, the Mediterranean has been identified as a region with a strong coupling between the atmosphere and the land surface, with feedback effects of soil moisture on temperature and precipitation (Seneviratne et al, 2010;Knist et al, 2017;Hertig et al, 2019). Indeed, soil moisture is a key variable in the hydrological cycle for the partitioning of rainfall into infiltration and runoff and also for the mass and energy balance between land surface and the atmosphere (Seneviratne et al, 2010;Brocca et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The Mediterranean region is a transitional zone between dry and wet climates, and in these semiarid areas the direct evaporation from the soil plays an important role on the surface energy balance, with evapotranspiration strongly dependent on available soil moisture (Koster et al, 2004;Seneviratne et al, 2010;Taylor, 2015). Consequently, the Mediterranean has been identified as a region with a strong coupling between the atmosphere and the land surface, with feedback effects of soil moisture on temperature and precipitation (Seneviratne et al, 2010;Knist et al, 2017;Hertig et al, 2019). Indeed, soil moisture is a key variable in the hydrological cycle for the partitioning of rainfall into infiltration and runoff and also for the mass and energy balance between land surface and the atmosphere (Seneviratne et al, 2010;Brocca et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the entire hydrological model chain ( Figure 3) is run with all possible combinations of perturbed daily temperature and precipitation time series generated for the sensitivity analysis (Equations (8) and (9)), and the result of each combination (i.e., the mean impact) is plotted as one single realization (i.e., one pixel) of possible climate change impacts in a two-dimensional domain (i.e., the response surface with 11 × 11 = 121 realizations, thus including the reference pixel, i.e., the realization with non-perturbed, original input data). This so-called scenario-neutral approach was introduced by Prudhomme et al [69] and has been applied for various purposes [1,70]. In that way, this approach differs from top-down approaches that apply an ensemble of (locally adjusted) GCM-RCMs as inputs into the hydrological model.…”
Section: Sensitivity Analysis and Response Surfacesmentioning
confidence: 99%
“…In this study, we apply simple linear scaling to the meteorological input data, as shown in Equations (8) and 9, although this neglects possible modifications of the temporal structure of the input and response data due to climate change [1,70]. This limitation is similar to the criticism raised against delta change approaches for statistical downscaling in top-down approaches [72].…”
Section: Sensitivity Analysis and Response Surfacesmentioning
confidence: 99%
“…To overcome the uncertainties and problems associated with model cascades, alternative approaches are currently being developed (Guo et al, 2017;Knighton et al, 2017;Kim et al, 2018;Broderick et al, 2019;Keller et al, 2019a;Keller et al, 2019b). In studies investigating the impacts of climate change on hydrology, a scenario-neutral approach has been used to analyze the sensitivity of river flows to changes in temperature and precipitation, where the observed rainfall and temperature data are modified by stepwise increases or decreases in the value of associated parameters.…”
Section: Introductionmentioning
confidence: 99%